A Method for Detecting Circulating Tumor Cells Based on the Measurement of Single‐Cell Metabolism in Droplet‐Based Microfluidics. Issue 30 (1st June 2016) - Del Ben, Fabio; Turetta, Matteo; Celetti, Giorgia; Piruska, Aigars; Bulfoni, Michela; Cesselli, Daniela; Huck, Wilhelm T. S.; Scoles, Giacinto
Abstract: The number of circulating tumor cells (CTCs) in blood is strongly correlated with the progress of metastatic cancer. Current methods to detect CTCs are based on immunostaining or discrimination of physical properties. Herein, a label‐free method is presented exploiting the abnormal metabolic behavior of cancer cells. A single‐cell analysis technique is used to measure the secretion of acid from individual living tumor cells compartmentalized in microfluidically prepared, monodisperse, picoliter (pL) droplets. As few as 10 tumor cells can be detected in a background of 200 000 white blood cells and proof‐of‐concept data is shown on the detection of CTCs in the blood of metastatic patients. Abstract : An altered metabolism is one of the hallmarks of cancer cells. Differences between healthy and cancerous cell metabolism, hidden in bulk, are apparent in tiny (pL) droplets containing individual cells. Within minutes, cancerous cells generate a pH change in their microenvironment. By measuring the pH value in each droplet, circulating tumor cells (CTCs) can be detected in patient samples. WBC=white blood cell; lac=lactate.